Librarianship resizing due to the closure of libraries in Ecuador: The case of a public library - Quiroz Gonzalez, Yulexy Karolina (2024)
The closure of libraries in Ecuador severely impacts low-income populations who rely on these spaces for access to books, computers, and the internet. In the absence of these services, many users are forced to resort to self-learning and the autonomous adoption of technologies, which exacerbates inequality in access to information. This research aims to analyze the effects of the closure of the library in the Crucita parish, located in the Portoviejo-Manabí canton. A descriptive study with a quantitative approach was conducted. The documentary analysis method was employed, allowing for a deeper examination of the subject through the review of relevant sources. Additionally, a survey was administered to a portion of the Crucita population. The results showed that the population recognizes the importance of libraries and their necessity, as they lack access to one to carry out various activities. Furthermore, there is a positive stance regarding the interest in the repositioning or establishment of a public library. In conclusion, the need to implement libraries to improve access to information for the Ecuadorian population is emphasized, as this would foster a knowledge-based culture that promotes the country’s social and economic progress.